Barriers and facilitators to intradialytic parenteral nutrition implementation targeting protein energy wasting in Malaysian hemodialysis patients - Birinder Kaur Sadu Singh; Khor, Ban-Hock; Sharmela Sahathevan; Abdul Halim Abdul Gafor; Enrico Fiaccadori; Karuthan Chinna; Ng, See-Hoe; Tilakavati Karupaiah (Multidisciplinary Digital Publishing Institute, 2022)
The capacity to deliver intradialytic parenteral nutrition (IDPN) for patients on hemodialysis (HD) diagnosed with protein energy wasting (PEW) in low resource settings is unknown. This study aimed to examine the extent of IDPN practice in HD units in Malaysia, and its implementation to treat PEW. We surveyed pharmacists (n = 56), who are central to parenteral nutrition delivery in Malaysia including IDPN. Seventeen healthcare stakeholders engaging with the Promoting Action on Research Implementation in Health Services (PARIHS) framework used the Likert scale to rate survey outcomes on IDPN implementation to treat PEW, according to the Evidence, Context, and Facilitation elements. IDPN for HD patients was available in 28 of 56 hospitals providing parenteral nutrition services, with only 13 hospitals (23.2%) providing IDPN to outpatients. Outpatient treatment was concentrated to urban locations (12/13) and significantly associated (p < 0.001) with resident nephrologists. The Evidence domain was rated poorly (2.18 ± 0.15) pertaining to IDPN indication when the oral spontaneous intake was ≤20 kcal/kg/day. The Context domain indicated good adherence to international best practice relating to IDPN administration (4.59 ± 0.15) and infusion time (4.59 ± 0.12). Poor adherence was observed in the Facilitation domain on ’Access to pharmacist and dietitian at HD units’ (2.65 ± 0.21) and ’Access to continuous medical education on managing PEW patients on HD’ (2.53 ± 0.15). The IDPN outpatient service was concentrated to urban hospitals with greater manpower resources. The PARIHS evaluation on IDPN implementation to treat PEW revealed facilitators in good practice adherence for prescribing and administration of IDPN but highlighted major barriers relating to IDPN indication and nutrient calculation.